PAI and Anti-Corruption Issues: Analysis of Strategy for Development of PAI Materials Based on Ahlussunnah Wal Jama'ah - M. Sayyidul Abrori; M. Makhrus Ali (Journal of Research in Islamic Education, 2023)
There are still many problems in Indonesia, ranging from poverty rates, lack of equal distribution of education to corrupt behavior. The existence of perpetrators of corruption because of the encouragement that someone has in the inability to control himself. Thus there is a corruption deviation that leads to the decline of human dignity. So it is necessary to have an anti-corruption attitude based on Aswaja which is instilled in students from an early age. This is expected that students are not only intelligent in cognitive terms but affective intelligence is also formed so that students are able to become insan kamil This research method uses descriptive qualitative using Thomas Lickona's character education theory. The design of PAI (Islamic Education) and the issue of anti-corruption in this paper is by inserting anti-corruption material into existing material in KI (Core Competence) and KD (Basic Competence). Thus students are able to analyze the problems that exist in reality using Islamic religious teachings contained in the Koran. There are two models to participate in the corruption eradication and prevention movement, namely,First, the educational process must foster socio-normative awareness, build objective reasoning and develop a universal perspective on the individual.Second, education must lead to strategic seeding, namely the personal qualities of individuals who are consistent and solid in their social role engagement.